Prospects for studying the history of the newspapers “Keräşen süze” and “Tuganaylar” - Emil I. Sharafiev (Историческая этнология)
The article is intended to identify the promising areas in studying the historical development of the newspapers Keräşen süze and Tuganaylar. It provides a historiographical overview of the topic, as well as substantiates its novelty and theoretical significance. The paper provides brief general information on the history of the newspapers Keräşen süze and Tuganaylar and reveals their significance and the functional and socio-cultural meaning. Particular attention is paid to defining the problem field and highlighting the poorly studied aspects of the topic: dynamics of institutional development, correlation with other socio-cultural and socio-political processes among the Kryashens, the editorial staff, periodization, conflict situations, editorial mail, the financial situation. The author has articulated a number of research questions, answering which he believes to be important when considering one or another of the topic aspects. It is noted that the history of periodicals of the Kryashens in the post-Soviet period is in close and inextricable connection to the problem of the Kryashen journalism development at the relevant time, which also has a number of aspects and has not yet become the subject of special scholarly research.